(untitled) (SAARC Journal of Agriculture, 2024)
An experiment was conducted with seven drought tolerant rice varieties i.e., Binadhan-17, Binadhan-19, BRRI dhan56, BRRI dhan57, BRRI dhan66, BRRI dhan71 and BRRI dhan83 were used as plant materialism. Boro season during December 2022-May 2023 to evaluate the yield performance at the reproductive stage as well as disclose the inherent variability of the varieties for yield and yield attributing traits following a randomized complete block design with three replications. Significant variation (p<0.01) was observed for genotype, treatment and G (genotype) × T (treatment) interactions viz., days to maturity, plant height, effective tillers/plant, filled grains/plant, unfilled grains/plant, 100-seed weight, grain yield/plant and H2O2. Drought stress lead to a significant decrease in grain yield/plant in all of the varieties; highest decrease was found in BRRI dhan56 (48.65%) followed by BRRI dhan57, BRRI dhan66, Binadhan-17, Binadhan-19, BRRI dhan83, and BRRI dhan71 (42.08, 39.01, 37.58, 34.54, 32.28 and 31.92%, respectively) related to control. Interestingly, the highest yield was recorded in Binadhan-17. Principle component analysis revealed that the first two components explained 76.1% of the total variations of the studied varieties, indicating total tillers/plant, effective tillers/plant, filled grains/plant, 100-seed weight and grain yield/plant are the most important characters contributing to yield. Grain yield/plant showed significant positive correlation with total tillers/plant, effective tillers/plant, filled grains/plant, 100 seed weight. From stress tolerance indices Binadhan-17 was categorized as tolerant genotype with superior yield performance and this genotype was selected for further study under different drought prone areas of Bangladesh as well as for genetic improvement against drought stress. SAARC J. Agric., 22(1): 73-84 (2024)